Web 3.0 and medicine - Giustini, Dean (BMJ. British medical journal (Clinical research ed.), 2008)
[...]medical librarians are leading doctors back to trusted sources, such as PubMed, Clinical Evidence, and the Cochrane Library, and even taking them to their library bookshelves instead. [...]greater capacity for creating knowledge in medicine will be possible if we have the will to publish clinical data openly and transparently, and subject it to scrutiny. 7 Developing a more personalised healthcare system will be an important challenge for doctors in web 3.0.